KONTRUKSI REALITAS DI TENGAH KABUT ASAP: ANALISIS FRAMING KEBAKARAN HUTAN SUMATERA DI PROVINSI RIAU OLEH KOMPAS.COM DAN TRIBUN PEKANBARU.COM - Farah Faza; Erni Hartini; Arief Vian; Fadly Ardyan; Bryan Alvian; Aisyah Inas; Richo Ilham; Gianjar Wasito Adi; Malik Ibrahim (Nusantara Hasana Journal, 2026)
This study analyzes the differences in the construction of the reality of forest and land fires (karhutla) in Riau Province between KOMPAS.com and Tribun Pekanbaru.com. The novelty of this study lies in the systematic comparison between media from two different hierarchical levels, which has not been widely done in studies of forest fire framing in Indonesia, as well as the explicit integration of framing analysis with Berger and Luckmann's theory of social reality construction. The study uses a qualitative approach with the framing analysis method of Zhongdang Pan and Gerald M. Kosicki's model, which dissects news texts into four structures: syntactic, script, thematic, and rhetorical. The primary data sources are eight news articles published between February and April 2026, selected purposively from both media. The analysis results show that KOMPAS.com frames karhutla as an ecological and environmental conservation issue triggered by natural factors such as dry weather and peat conditions, by emphasizing scientific data and the institutional resilience of Manggala Agni. In contrast, Tribun Pekanbaru.com frames forest and land fires as an ongoing, uncontrolled crisis, emphasizing the recurring cycle of fires, the failure of initial suppression efforts, and the direct impact on the lives of villagers. This difference in framing reflects the influence of each media outlet's geographic location, emotional proximity to the event, audience size, and editorial orientation. This study concludes that both media outlets direct readers toward a naturalization of the disaster and amplification of the heroic discourse of officials in the field, while simultaneously ignoring structural factors such as the role of corporations, land conversion, and weak law enforcement. Thus, the reality of forest fires is constructed differently depending on the media hierarchy, with KOMPAS.com tending to construct narratives from the perspective of central policy and official data, while constructing reality from the perspective of the community's direct experience amidst the haze.